Mengejawantahkan Metode Istimbath Al-Ahkam Berbasis Maqāshid Al-Syarī’ah Dalam Menjawab Persoalan Kekinian - Moh. Mujibur Rohman; Rohman Rohman; Taufikurrahman Taufikurrahman (Qisth : Jurnal Studi dan Penelitian Hukum Islam, 2026)
The development of the era marked by the complexity of social, cultural, economic, and technological issues requires a re-reading of the sharia arguments to keep them relevant and contextual. Contemporary issues are often not found explicitly in the texts of the Qur'an and al-Sunnah, so a methodological approach is needed that can bridge the gap between normative texts and empirical reality. In this context, maqāṣid al-syarī‘ah becomes an important conceptual framework for realizing the sharia arguments substantively and oriented towards the welfare of the people. This approach emphasizes that the main objective of sharia is to maintain and realize the fundamental values ​​of human life, such as justice, humanity, and the public welfare. The problem formulation in this article includes: how the concept of maqāṣid al-syarī‘ah can be used as an approach in understanding and realizing the sharia arguments; and to what extent the maqāṣid approach is able to provide solutions to contemporary problems without ignoring the authority of sharia texts. The purpose of writing this article is to analyze the urgency of maqāṣid al-syarī‘ah as a paradigm of contemporary ijtihad, and explain its role in responding to the challenges of Islamic law in the modern era in a proportional and responsible manner. The research methodology used is normative Islamic law research with a conceptual approach and a philosophical approach. Data sourced from primary legal materials in the form of the Qur'an and al-Sunnah, as well as secondary legal materials in the form of works of classical and contemporary scholars who discuss maqāṣid al-syarī‘ah and ushul fiqh. Data analysis was conducted qualitatively-descriptively with an emphasis on deductive reasoning to draw conclusions regarding the relevance and implementation of sharia arguments based on maqāṣid al-syarī‘ah in addressing contemporary problems.